Institutional Policy for Child Safeguarding as a Mechanism for Improving the Child Protection System in Violence in State Institutions of The Republic of Serbia and Bosnia and Herzegovina - Branković, Iva; Tanasijević, Jelena (Zbornik Instituta za kriminološka i sociološka istraživanja, 2022)
Violence against children is one of the most serious forms of violation of basic human rights. Significant efforts have been made in Bosnia and Herzegovina and the Republic of Serbia to protect children from violence at the systemic level, but these processes, as well as their effects, have not been thoroughly evaluated so far. In order to review and better understand the context for the protection of children from violence in institutions, an analysis was conducted in which the normative and strategic framework in both countries was critically reviewed. The goal of this paper is to present the results of the analysis, which indicate the existence of a good basis in the normative and strategic framework, but also the need to strengthen the capacity of institutions through improving existing procedures, introducing child safeguarding policies and improving competencies of professionals to recognize and respond to situations in which the safety of children is at risk.